Working memory capacity, disembedding ability and problem solving techniques among college students in physics - Vallente, Amancia Ragandac (Animo Repository, 2004)
This qualitative study describes the problem solving techniques used by students of different levels of working memory capacity and disembedding ability in solving two forms of problems in Mechanics: 1) conventional question with the information entirely as a text and 2) given data are presented almost wholly in a diagram. Four problems, two of which involved one-body problems along the horizontal and the other two, two-body problems, were prepared and validated. The working memory capacity and disembedding ability of the 100 second year engineering students enrolled in Physics 105 during the first semester of SY 2003-2004 at the College of Arts and Sciences, Mariano Marcos State University, Batac, Ilocos Norte were assessed through the use of the Digit Backward Test and Find-A-Shape-Puzzle, respectively. The mean and the frequency distribution of the students' score in each test were used as a basis in classifying the levels of working memory capacity and disembedding ability of the students. Four groups of students were formed. These groups correspond to the four possible combination of their levels which were as follows: 1) High Processor-Field Independent Students, 2) High Processor-Field Dependent Students, 3) Low Processor-Field Independent Students, and 4) Low Processor-Field Dependent Students. Two students from each group were chosen randomly as respondents. These eight students solved the four problems in mechanics. The students verbalized their thoughts while they were solving and these were audio and video recorded. For further clarification and verification of students' solution, the students were individually interviewed after the problem solving session. The techniques employed by the students were determined by coding their written solution as well as the transcripts of their recorded verbalized thoughts. Students' performance was determined through rubric scoring of their written solution. Students seem to rely most of the time on equations they remembered from examples cited by their teachers rather than through the free-body diagram. The high processor-field independent students showed a more organized way of solving problems than the rest. As regards their performance, it was observed that the extremes of performance in both forms of the problems occurred between field independent students with high working memory capacity and field dependent students with low working memory capacity. Students of low working memory capacity but of high disembedding ability obtained higher marks in both forms of the problem than students of high working memory capacity but of low disembedding ability. This implies that these low working memory capacity students are working at their potential because their working memory spaces are occupied only by relevant materials. Thus, disembedding ability is a significant factor in influencing performance of students. Results seem to underscore that the students of the same as well as of different levels of working memory capacity and disembedding ability use different techniques in solving a problem.